Selective Reduction of a,b-Unsaturated Steroidal Carbonyl Compounds by NaBH4 in Presence of Guanidine Hydrochloride in Dioxane - Ahmad Khan, Salman; M. Asiri, Abdullah (Asian Journal of Chemistry, 2014)
A selective hydrogenation of a,b-unsaturated steroidal carbonyl compounds with NaBH4 in the presence of guanidine hydrochloride in dioxane in good to excellent yields are described.